The relationship between risk experience and risk response: a study of farmers and climate change. Issue 11 (2nd November 2017) - Hamilton-Webb, Alice; Manning, Louise; Naylor, Rhiannon; Conway, John
Abstract : Within the existing literature, the role of experience of risk on attitudinal and behavioural risk response has been relatively neglected. Recent research that draws on the psychological distance of climate change as a concept notes the importance of local, significant experience as a driver for encouraging appropriate response. The experience of flooding was used as the stimulus in this paper, and emphasis placed on whether direct and/or indirect experience of flood risk is associated with different responses to climate change risk. In order to explore the relationship between climate change risk experience and response in the form of on-farm mitigation and adaptation, this paper draws on a case study of farmers in England, many of whom have experienced flooding. Results from a quantitative survey undertaken with 200 farmers in Gloucestershire, England are discussed. Statistical analysis found experience of flooding to be significantly associated with a heightened concern for climate change. Although also finding an association between experience and behavioural response, the sample were most likely to be taking adaptive behaviour as part of normal practice, with factors such as lack of overall concern for climate change risk and absence of information and advice likely to be the main barriers to action. Risk communication needs to further emphasise the connection between climate change and extreme weather events to allow for farmers to perceive climate change as a relevant and locally salient phenomenon, and subsequent tailored information and advice should be offered to clearly illustrate the best means of on-farm response. Where possible, emphasis must be placed on actions that also enable adaptation to other, more immediate risks which farmers in this study more readily exhibited concern for, such as market volatility.